La circoncision, le tatouage, les rituels du hammam dans la littérature marocaine d’expression française : Abdelkébir Khatibi et Tahar Ben Jelloun - Zdrada-Cok, Magdalena (Romanica Silesiana)
This article compares the functions of rituals in the novels of Abdelkebir Khatibi and Tahar Ben Jelloun (La mémoire tatouée, Harrouda, L’Enfant de sable, La Nuit sacrée). The aim of the study is to show that Abdelkebir Khatibi and Tahar Ben Jelloun represent the traditional rituals of the body as elements of a hybrid language (corpslangue). This “language tattooed on the body” expresses the plurality of the North African culture and the contradictions of Moroccan society. It shows the Moroccan individual torn between the loyalty to tradition and the need for transgression. Key words: Moroccan culture, rituals, tradition, transgression